2014
DOI: 10.14503/thij-12-2853
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab-Vincristine Chemotherapy-Induced Acute Anterior Wall Myocardial Infarction with Cardiogenic Shock

Abstract: 1 Chemotherapy-induced left ventricular (LV) dysfunction is often encountered in clinical practice, but chemotherapy-mediated ischemic syndromes are rarely seen. The incidence of acute myocardial infarction (AMI) after chemotherapy varies from 1% to 5%.1 We describe the case of an elderly man with non-Hodgkin lymphoma (NHL) who developed AMI after the administration of chemotherapeutic agents. Case ReportA 68-year-old man with coronary artery disease (CAD) and severe single-vessel disease of the left anterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…93 In some case reports, cardiac adverse events were correlated with rituximab infusion for oncohematological disorders, in combination with other chemotherapeutic agents. 94,95 Similar data were found for autoimmune diseases, 96,97 even if, recently, a large cohort study found that rates of cardiac (and stroke) events in RA subjects treated with rituximab were consistent with rates found in general RA population in an 11-year follow-up. 98 Another monoclonal antibody used in RA is tocilizumab, an anti-IL-6 receptor antibody.…”
Section: Monoclonal Antibodiessupporting
confidence: 62%
“…93 In some case reports, cardiac adverse events were correlated with rituximab infusion for oncohematological disorders, in combination with other chemotherapeutic agents. 94,95 Similar data were found for autoimmune diseases, 96,97 even if, recently, a large cohort study found that rates of cardiac (and stroke) events in RA subjects treated with rituximab were consistent with rates found in general RA population in an 11-year follow-up. 98 Another monoclonal antibody used in RA is tocilizumab, an anti-IL-6 receptor antibody.…”
Section: Monoclonal Antibodiessupporting
confidence: 62%
“…We considered a convenience sample of 10 patients from our heart failure clinic since the previously reported incidence of acute coronary syndrome (ACS) and atrial and ventricular arrhythmias with the use of rituximab is <0.1% and 7.6%, respectively 8. Regarding the worsening of left ventricle ejection fraction (LVEF) attributed to rituximab, the incidence is limited to case reports only, wherefore it is impossible to precisely determine the incidence 9.…”
Section: Methodsmentioning
confidence: 99%
“…There have been multiple case reports of acute coronary events precipitated by infusion of various chemotherapeutic agents [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Several mechanisms have been proposed, including vasospastic phenomena, endothelial and mitochondrial cytotoxicity, cell-cycle arrest of cardiac endothelial cells, and even release of cytokines leading to plaque rupture and platelet activation [14,15,[18][19][20][21]. The variability in proposed mechanisms reflects the variability in site of action and downstream effects of cancer-specific treatment leading to ischemia.…”
Section: Current Experiencementioning
confidence: 99%